Anodic Stripping Voltammetric Determination of Lead (II) and Cadmium (II) by Using a Carbon Nanotubes Paste Electrode Modified with Ion Exchange Synthetic Resin - de Oliveira, Paulo Roberto; Stradiotto, Nelson Ramos [UNESP]; Tanaka, Auro Atsushi; Bergamini, Marcio F. (Bentham Science Publ Ltd, 2012)
This work describes an electroanalytical method for simultaneous determination of cadmium (II) and lead (II) ions using a carbon paste modified with carbon nanotubes and an ion exchange synthetic resin (Amberlite IR120) electrode under Differential Pulse Anodic stripping voltammetric (DPASV) conditions. The procedure is based on the effective preconcentration of metal ions on the electrode surface containing ion exchange resin under open circuit condition. Using optimized conditions of 600 s preconcentration time for an electrode composition of 5% w/w Amberlite IR 120 and 30 % w/w carbon nanotubes in the paste, a scan rate of 10 mVs(-1), and a potential pulse amplitude of 75 mV, linear calibration graphs can be obtained by were monitoring the peaks at -0.75 V for cadmium (II) and -0.58 V for lead (II) from 0.07 - 2.50 mu mol L-1 and 0.01 - 5.80 mu mol L-1, respectively. The proposed method was applied for the determination of lead (II) and cadmium (II) in ethanol fuel, gasoline for aviation, and spiked water. For all samples analyzed, recoveries ranged from 95.8 to 106.3%. Interferences were also evaluated.
Keywords: Cadmium determination; Carbon nanotubes Paste Electrode; Ethanol Fuel; Gasoline for aviation; Amberlite IR120; Lead determination; Stripping analysis; Voltammetric sensors